Odpowiedzi

Najlepsza Odpowiedź!
2010-02-28T19:13:48+01:00
¼ - ½ =1/4-2/4=-1/4
(-3 i 1/5 ) - 2½ = -16/5-5/2=-32/10-25/10=-57/10= -5 7/10
1⅙ - (2 i 1/12) = 7/6-25/12= 14/12-25/12=-11/12
3,7 - 4⅖ = 37/10-22/5=37/10-44/10= -7/10
(-2⅙) - (- 1,6) =-13/6+16/10=-65/30+48/30= -17/30
1,4 - (-1¾) =56/40+70/40=126/40=3 3/20
1 5 1
2010-02-28T19:16:32+01:00
¼-½ = ¼ - 2/4 = - ¼
(-3 i 1/5 ) - 2½ = -3 2/10 - 2 5/10 = - 5 7/10
1⅙ - (2 i 1/12) = 1 2/12 - 2 1/12 = - 1 1/12
3,7 - 4⅖ = 37/10 - 44/10 = -7/10
(-2⅙) - (- 1,6) = -2 1/6 + 1 6/10 = -2 5/30 + 1 18/30 = - 65/30 + 48/30 = - 17/30
1,4 - (-1¾) = 1 4/10 + 1 3/4 = 1 8/20 + 1 15/20 = 3 3/20
2010-02-28T19:29:04+01:00
¼ - ½ =1/4-2/4=-1/4
(-3 i 1/5 ) - 2½ =-3 2/10-2 5/10=-5 7/10
1⅙ - (2 i 1/12) =1 2/12-2 1/12=-11/12
3,7 - 4⅖ =3 7/10-4 4/10=-7/10
(-2⅙) - (- 1,6) =-2 5/30+1 18/30=-17/30
1,4 - (-1¾) =1 4/10+1 3/4=1 8/20+1 15/20=3 3/20